OCT-Precoding Combined with LDPC-Coding Scheme for 128 QAM MB-OFDM UWBoF System - Changqing Xiang; Xi Yang; Xiaojun Zhu; Qiong He; Renmin Zhang; Zhiyang Xiang (Advances in Condensed Matter Physics)
In this paper, we proposed a coding scheme based on orthogonal cyclic transpose (OCT) precoding combined with low-density parity check (LDPC) code to improve the transmission performance of 128-quadrature amplitude modulation multiband orthogonal-frequency-division-multiplexing ultrawide band over fiber (128 QAM MB-OFDM UWBoF) system. The proposed scheme could not only improve the performance of the system but also average the signal-to-noise ratio (SNR) of subcarriers and reduce the difference among subchannels in practical application. The simulation results showed that compared with the traditional scheme, the receiver performance of this scheme was improved by 2.7 dB when the LDPC-coding rate was 87.5% through 70 km standard single mode fiber (SSMF) transmission and the bit error rate (BER) was 3.8 × 10−3. Besides, the constellation distribution was more convergent and uniform.